The correlations of engineering characteristics of Johor coastal clay - Hasan, Muzamir (2006)
The characteristics of coastal clay soil are different compared to other soils due to their low strength and high compressibility. It is also difficult to get an undisturbed sample of this type of soil for laboratory testing. Hence, the correlation between engineering characteristics and basic properties or between engineering characteristics itself will be useful to engineers especially for preliminary design purposes. This paper presents some correlations of engineering characteristic of coastal clay in Johor that is the clay taken from Port of Tanjung Pelepas and Pontian. An attempt was made to correlate the Atterberg limits with the shear strength and also the shear strength with depth. In general, the correlations show that the liquid limit and plasticity index increase with moisture content. The plasticity index also tends to increase with liquid limit. For the undrained shear strength it is found to increase with depth, and decreases with moisture content, liquid limit, and plasticity index. An attempt was also made to get correlation between the liquid limit with the clay content. It is found that the liquid limit increases with the increase of clay content, probably due to the clay particles tend to pull or absorb water to the surface of soil particle, making the liquid limit to be much higher. The results give an alternative for engineers to use the basic soil properties to predict the strength of soil. One can also determine the shear strength of the soil at certain depth below ground level. This will allows a quick and economic design for construction on soft clay